Biological soil crusts on patterned grounds and their influence on plant succession - Richter, Dorota; Pietryka, Mirosława; Fudali, Ewa (Polish Polar Research, 2025)
The taxonomical diversity of cyanobacterial-microalgal crusts (CMC) forming on various types of patterned grounds (PG) and their dependence on some environmental variables were studied. The research was carried out in southwestern Spitsbergen, Svalbard. In total, 82 taxa of cyanobacteria and 79 taxa of algae, 6 species of liverworts, 20 of mosses, 10 of angiosperms and 2 of lichens were identified. The species and quantitative composition of CMC on different PG types were different, and the differentiating factor was moisture. Distinctive for PG types of high sorting activity was the occurrence of string like grey-beige cyanobacteria crusts. A general pattern of changes in the structure of crusts have appeared, starting from the dominance of filamentous cyanobacteria with co-dominance of coccoid species, forming gelatinous sheats. Next, a decrease in their share, up to stop a forming crust in the phases with visible development of the plant cover were observed, although groups of filamentous green algae and diatoms still occurred. In addition, a relationship between taxonomic diversity of CMC and the diversity of subsequent plant cover was studied. A difference in dominance of some species of liverworts and mosses between the labyrinth and circle types of patterned grounds was noted and both of these types were taxonomically different in relation to CMC.